FOCI: Flexible organizer for competitive intelligence - ONG, Hwee-Leng (Institutional Knowledge at Singapore Management University, 2001)
This paper describes how an integrated web-based application, code-named FOCI (Flexible Organizer for Competitive Intelligence), can help the knowledge worker in the gathering, organizing, tracking, and dissemination of competitive intelligence or knowledge bases on the web. It shows how text mining techniques including a novel user-configurable clustering, trend analysis and visualization techniques can be used synergistically to address the problem of managing information gathered from the web. FOCI allows a user to define and personalize the organization of the information clusters according to their needs and preferences into portfolios. Predefined sections for organizing information in specific domains is also supported. The personalized portfolios created can be saved and subsequently tracked and shared with other users. In addition, FOCI is designed to handle multilingual documents.